The determination of some heavy metal and mineral levels in frozen shrimp and frozen squid - Canpolat, Özgür; Çağlar, Metin (My University, 2014)
In this study, the levels of some heavy metals (copper, iron, zinc, cadmium, cobalt, nickel, lead, mercury and arsenic) and minerals (calcium and magnesium) were determined in three different brands of frozen shrimp and frozen squid samples available in local markets of Elazig (Turkey). Concentrations of elements were determined by Inductively Coupled Plasma (ICP). Only Cu, Fe, Zn, Cd, Ca and Mg were detected in frozen shrimp and frozen squid samples analyzed. Co, Ni, As, Hg and Pb were found to be undetectable levels in all samples. Heavy metal and mineral levels in frozen shrimp were found to be in range of 2.27-5.24 ppm for copper, 1.62-4.62 ppm for iron, 2.12-7.28 ppm for zinc, 0.02-0.09 ppm for cadmium, 1.03-1.98 ppm for calcium and 1.00-1.92 ppm for magnesium. Heavy metals and minerals in frozen squids were found to be in range of 1.22-3.39 ppm for copper, 2.84-6.97 ppm for iron, 2.19-6.29 ppm for zinc, 0.04-0.1 ppm for cadmium, 1.00-1.96 ppm for calcium and 1.01-1.99 ppm for magnesium. These results show that heavy metal levels in the frozen shrimp and frozen squid samples were under the dangerous limits given by WHO and FAO and there is no any risk for public health by consuming.

Bu çalışmada, Elazığ (Türkiye)’da yerel marketlerden elde edilen üç farklı firmaya ait dondurulmuş karides ve kalamarda bazı ağır metallerin (bakır, demir, çinko, kadmiyum, kobalt, nikel, kurşun, civa ve arsenik) ve minerallerin (kalsiyum ve magnezyum) düzeyleri İndüktif Eşleşmiş Plazma (ICP) ile belirlenmiştir. Dondurulmuş karides ve kalamarda sadece Cu, Fe, Zn, Cd, Ca ve Mg düzeyleri belirlenirken, bütün örneklerde Co, Ni, As, Hg ve Pb düzeyleri cihazın okuma duyarlılığının altında olduğundan tespit edilememiştir. Dondurulmuş karidesde bazı ağır metallerin ve minerallerin düzeyleri bakır 2.27-5.24 ppm, demir 1.62-4.62 ppm, çinko 2.12-7.28 ppm, kadmiyum 0.02-0.09 ppm, kalsiyum 1.03-1.98 ppm ve magnezyum 1.00-1.92 ppm olarak bulunmuştur. Dondurulmuş kalamarda ise bazı ağır metal ve mineral düzeyleri bakır 1.22-3.39 ppm, demir 2.84-6.97 ppm, çinko 2.19-6.29 ppm, kadmiyum 0.04-0.1 ppm, kalsiyum 1.00-1.96 ppm ve magnezyum 1.01-1.99 ppm olarak belirlenmiştir. Dondurulmuş karides ve kalamar için verilen bu ağır metal düzeylerinin WHO ve FAO tarafından verilen değerlerin altında olduğu ve insanlar tarafından tüketildiğinde sağlık açısından bir risk oluşturmadığı tespit edilmiştir
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Frozen shrimp; Frozen squid; Heavy metals; Minerals; Elazig; Turkey; Dondurulmuş karides; Dondurulmuş kalamar; Ağır metal; Mineral madde; Elazığ; Türkiye